Manganyi, Calvin/Liebenberg, Ian/Potgieter, Thean (eds), South Africa and Romania: transition to democracy and changing security paradigms. Durban: Just Done Productions 2013, 376 pp. (The Strategic Review for Southern Africa, 2020)
This volume is based on NRF-funded research cooperation between the Institute for Political Studies of Defence and Military History in Bucharest and the Faculty of Military Science at Stellenbosch University, dealing with the transition from authoritarian rule to democracy. It discusses the transition to multi-party democracy, the consequent changes in the security environment and the current role and defensive posture of these countries in their respective regions. All contributions are abstracted separately in the introductory chapter (pp 1-11). The specific chapters discuss the joint experiences and challenges in facing the transition from authoritarian rule to democracy (1. Liebenberg, I: "Transition from Authoritarian Rule to Democracy": 13-36; 2. Sasz, P V: "Transition to Democracy in Romania": 37-57; 4. Mangayani, C: "The Role of Youth in South Africa's Transition": 87-121), the reform of the armies (3. Ionesco, M: "Transition, Alliances and Military Reform in Romania in the post-Cold War Period": 59-86; 5. Ferreira, R: "South Africa: From Apartheid Army to a Post-Apartheid Defence Force": 123-135; 7. Mangayani, C: "Structures for Political Oversight of the Military": 171-204; 8. Otu, P: "Military Reform in Romania": 205-231) as well as the repositioning of Romania's security strategy (6. Cioculescu, S: "Romania's National Security Strategy in the Post-Cold War Period": 137-170). South Africa's change in strategy concerning its interests in the Indian Ocean is the main focus of T Potgieter in chapter 10 (pp 267-305)and Romania's status within the Euro-Atlantic security architecture after the end of the Cold War and its entry into the North Atlantic Treaty Organisation (NATO) and the European Union (EU) has been dealt with by Carmen Rijnoveanu in chapter 11 (pp307-340). Worthy of special attention is chapter 9 (Liebenberg, I: "The Arms Industry, Reform and Civil-Military Relations in South Africa": 233-266), bridging the purchase of arms and ammunition during the inter-war years (1919-1939) to the period of World War II (1939-1945) and even further to the establishment of South Africa's own defence industry under apartheid rule (1948-1989), emphasising the enormous cost of maintaining a military superiority in southern Africa paving the way for South Africa's economic decline by the end of the 1980s and leading to the political demise of apartheid in the 1994 elections. In chapter 12 ("Waves of Change, Military-Political Reorientation, Economic Alliances and Uncertain Futures": 341-357), the editors make a comparison Strategic Review for Southern Africa, Vol 38, No 2 Book Reviews 181 of the different starting positions of both countries and the national security strategies that emerged from it.